Profile of head and neck neoplasms at a tertiary care centre in North India: two years pilot study (2018-2019) - Munjal, Manish; Rishi, Porshia; Tuli, Nitika; Singh, Harjinder; Talwar, Shivam; Sharma, Salony; Munjal, Shubham (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: In India 53,251 New Head and neck cancer cases are diagnosed every year. Oral cancer is the predominant subsite among both benign and malignant lesions. Methods: A retrospective study of cases with head and neck neoplastic lesions was conducted in department of otolaryngology, head and neck surgery, Dayanand Medical College and Hospital Ludhiana during for a period of 2 years (January 2018 to December 2019). Demographic, gender profile of the patients was studied. Results: Incidence of oral cancer was 21.5% followed by salivary glands 18.9%. among head and neck neoplasms over a period of 2 years (January 2018 to December 2019). The overall male to female ratio was 1:1.25, among benign was 1:1 and among malignant was 1:1.3. Conclusions: Commonest subsite of benign lesions was - oral cavity followed by salivary glands and larynx. Most common malignant subsite was oral cavity followed by larynx and thyroid. Male patients outnumbered the female. Mean age of presentation varied according to subsite.